Doporucení pro lécbu závislosti na tabáku - Králíková, E; Býma, S; Cífková, R; Ceska, R; Dvorák, V; Hamanová, J; Horký, K; Hradec, J; Keller, O; Konstacký, S; Kos, S; Kostrica, R; et al. (Casopis lekaru ceskych, 2005)
This first Czech version of guidelines formulated by the working group of mentioned medical associations is based on current literature and international guidelines. They are aimed mainly on clinical medicine and on incorporation of this treatment into the health care system according to WHO recommendations. They should serve to the treatment of tobacco dependence at any level: during any contact with the smoking patient (short intervention), in specialised centres or for the health care providers or health system itself.
Keywords: Tobacco Use Disorder; poruchy vyvolané užíváním tabáku; lidé; Humans